Description and outcome of dogs with primary immune‐mediated polyarthritis: 73 cases (2012‐2017). (2nd November 2022) - Ravicini, S.; Kent, A.; Dunning, M.; Baines, S.; Clarke, S.; Allerton, F.
Abstract : Objectives: To provide a description of primary idiopathic immune‐mediated polyarthritis, including long‐term outcome and relapse rates, for dogs starting treatment with corticosteroids alone or corticosteroids with a second immunosuppressant. Materials and Methods: Medical records were reviewed between January 2012 and December 2017 to identify dogs diagnosed with primary immune‐mediated polyarthritis. Data including signalment, clinicopathological findings, type and duration of treatment, relapse and outcome were recorded. Results: Seventy‐three dogs were included. Fifty‐four dogs were started on corticosteroid monotherapy (an additional immunosuppressant was introduced later in 27/54 dogs) and 19 dogs were treated with multi‐modal immunosuppression from the outset. Ninety‐five percent (69/73) of dogs responded favourably to therapy although death was attributed to immune‐mediated polyarthritis in 19% (14/73) of dogs. Relapse of clinical signs was reported in 53% (39/73) dogs (31/39 while on treatment), with multiple relapses observed in 17 dogs. Complete cure (permanent withdrawal of immunosuppressive medication) was achieved in 46 dogs (63%). Overall, 81% of dogs had a well‐managed disease for an extended timeframe (≥1131 days). Fourteen of 19 (74%) dogs that started treatment with multi‐modal immunosuppression and 32 of 54 (59%) started on corticosteroids alone achieved a complete cure. Clinical Significance: This study provides extended follow‐up information for a large cohort of dogs with primary immune‐mediated polyarthritis. Immunosuppressive therapy was discontinued in the majority of dogs but disease‐associated mortality remains high.